Pengelolaan PAUD Berbasis Experiential Learning - Pamungkas, Alim Harun; Sunarti, Vevi (Universitas Negeri Padang, 2018)
PAUD institutions are often interpreted as a place of learning for children who are only oriented to the skills and knowledge of reading, writing, counting, and drawing. PAUD institutions should focus on children's development related to religious and moral, physical, cognitive, language, social, emotional and artistic aspects. Thus the educational services provided by PAUD institutions must be able to facilitate all aspects of child development through enjoyable learning activities and help increase understanding of parents or the surrounding community about playing as a fun learning activity. Fun learning activities for early childhood need to be designed to help children get real life simulations in their daily activities. PAUD institution learning activities need to be adjusted to the stages of child development based on experiential learning model learning principles. On that basis, an activity is needed that facilitates the creation of learning experiences for managers and parents or community members in PAUD institutions about experiential learning.Keywords: Childhood Education (PAUD), Experiential Learning